Adipose Clocks: Burning the Midnight Oil - Henriksson, Emma (J Biol Rhythms, 2015)
Circadian clocks optimize the timing of physiological processes in synchrony with daily recurring and therefore predictable changes in the environment. Until the late 1990s, circadian clocks were thought to exist only in the central nervous systems of animals; elegant studies in cultured fibroblasts and using genetically encoded reporters in Drosophila melanogaster and in mice showed that clocks are ubiquitous and cell autonomous. These findings inspired investigations of the advantages construed by enabling each organ to independently adjust its function to the time of day. Studies of rhythmic gene expression in several organs suggested that peripheral organ clocks might play an important role in optimizing metabolic physiology by synchronizing tissue-intrinsic metabolic processes to cycles of nutrient availability and energy requirements. The effects of clock disruption in liver, pancreas, muscle, and adipose tissues support that hypothesis. Adipose tissues coordinate energy storage and utilization and modulate behavior and the physiology of other organs by secreting hormones known as “adipokines.” Due to behavior- and environment-driven diurnal variations in supply and demand for chemical and thermal energy, adipose tissues might represent an important peripheral location for coordinating circadian energy balance (intake, storage, and utilization) over the whole organism. Given the complexity of adipose cell types and depots, the sensitivity of adipose tissue biology to age and diet composition, and the plethora of known and yet-to-be-discovered adipokines and lipokines, we have just begun to scratch the surface of understanding the role of circadian clocks in adipose tissues.